Constant Frequency Torque Controller for DTC with Multilevel Inverter of Induction Machines - Norjulia, Mohamad Nordin; Naziha, Ahmad Azli; Nik Rumzi, Nik Idris; Nur Huda, Ramlan; Sutikno, Tole (Institute of Advanced Engineering and Science (IAES), 2016)
Direct Torque Control using multilevel inverter (DTC-MLI) with hysteresis controller suffers from high torque and flux ripple and variable switching frequency. In this paper, a constant frequency torque controller is proposed to enhance the DTC-MLI performance. The operational concepts of the constant switching frequency torque controller of a DTC-MLI system followed by the simulation results and analysis are presented. The proposed system significantly improves the DTC drive in terms of dynamic performance, smaller torque and flux ripple, and retains a constant switching frequency.